'Embracing Everybody': Approaching the Inclusive Early Childhood Education of a Child Labelled with Autism from a Social Relational Understanding of Disability. Issue 2 (June 2016) - Mackenzie, Meike; Cologon, Kathy; Fenech, Marianne
THIS STUDY INVESTIGATED EDUCATORS' attitudes towards the inclusion of a child labelled with autism in a mainstream early childhood education and care (ECEC) setting in Australia. The article provides an overview of three perspectives from which disability in inclusive early childhood education can be approached: the medical model of disability, the social model of disability and the social relational understanding of disability. Findings showed that when educators' beliefs and practices aligned with a social relational understanding of disability, inclusion for a child labelled with autism was facilitated. It is argued that inclusion in early childhood settings can be fostered when educators recognise and dismantle barriers to doing and barriers to being, and view inclusion as ordinary practice.